PENGARUH INTELLECTUAL CAPITAL DAN GOOD CORPORATE GOVERNANCE TERHADAP KINERJA KEUANGAN PADA BANK UMUM SYARIAH - Akmaludin, Akmaludin; Utami Putri, Arni; Sofiatul Huda, Sofi (KHITABAH: Khazanah Penelitian Perbankan Syariah, 2025)
This study examines the influence of Intellectual Capital and Good Corporate Governance (GCG) on the Financial Performance of Islamic Banks, considering the strategic role of banks in improving operational effectiveness and profitability. The urgency of this research arises from the gap between the potential of Intellectual Capital owned by banks and the implementation of optimal corporate governance practices, which directly impact financial performance. This quantitative research uses a documentary survey method on the quarterly financial reports of three Islamic banks (BSI, BTPN Syariah, and PNBS) for the period 2021–2024. Data analysis techniques applied include classical assumption tests, multiple linear regression, t-tests, F-tests, and correlation and determination coefficient analyses. The results of the study indicate that Intellectual Capital, Good Corporate Governance, and Financial Performance of Islamic banks are generally in the high category. Specifically, the findings indicate that: 1) Intellectual Capital has a positive and significant effect on financial performance. 2) Good Corporate Governance has a positive and significant effect on financial performance. 3) Intellectual Capital and GCG simultaneously have a significant effect on bank financial performance. The implications of this study emphasize the importance of maintaining and improving employee Intellectual Capital and implementing Good Corporate Governance practices to optimize financial performance and competitiveness of Islamic banks in a sustainable manner